Features of biology and cultivation of pikeperch (Sander lucioperca Linnaeus, 1758). Thematic bibliography - M. Simon; O. Polishchuk (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To provide a thematic bibliographic list of scientific publications that highlight the peculiarities of the biology and cultivation of pikeperch (Sander lucioperca Linnaeus, 1758) in Ukraine and the world.Accordingly, to combine classical and modern scientific works of domestic and foreign scientists.